Financial market frictions in a model of the euro area - Giovanni Lombardo; Peter McAdam (European Central Bank (ECB), 2012)
We build a model of the euro area incorporating financial market frictions at the level of firms and households. Entrepreneurs borrow from financial intermediaries in order to purchase business capital, in the spirit of the "financial accelerator" literature. We also introduce two types of households that differ in their degree of time preference. All households have preferences for housing services. The impatient households are faced with a collateral constraint that is a function of the value of their housing stock. Our aim is to provide a unified framework for policy analysis that emphasizes financial market frictions alongside the more traditional model channels. The model is estimated by Bayesian methods using euro area aggregate data and model properties are illustrated with simulation and conditional variance and historical shock decomposition.
Keywords: C11; C32; E32; E37; 330; Bayesian estimation; decompositions; DSGE modeling; euro area; Financial Frictions; Simulation